Draft Annual Plan 1994-95 Union Territory of Chandigarh - Planning Commission (Planning Commission, 1994)
Efforts have been made to make adequate provision for the developmental schemes of the Rural Sector. Schemes for the provision of basic amenities in the Rural Area have been included in the Annual Plan 1994-95. Special attention has been given to the needs of the economically weaker sections of the society. In line with the Government of India's Approach, an effort has been made to see that the development is augmented by growth in employment opportunities. Chandigarh is a planned city, it has all the modern amenities, such as. electricity, water supply, sewerage, storm water drainage/Roads etc. Health and Education facilities are also excellent here. However, because of the increase in its population
Planning & Evaluation Organisation, Finance Department